KARYOLOGICAL AND MORPHOLOGICAL VARIATIONS WITHIN Bassia hirsuta (L.) ASCH. IN BULGARIA - Mima Hristova Todorova; Neli Hristova Grozeva (Trakya University Journal of Natural Sciences, 2015)
This study was performed to determine karyological and morphological variability within and between populations of Bassia hirsuta in Bulgaria and to reveal their ecological preferences and detailed morphological characteristics. The studied Bulgarian B. hirsuta populations have diploid chromosome number 2n=18. The interpopulation variability which could be due to differences in ecological conditions is dominant. Vegetative traits are more variable than generative ones. The least variable are those that characterize the seed and could be used as highest value traits. The data given in the present study are supplementary to the data given about the species in Flora of the People’s Republic of Bulgaria and can be used both for correct identifications of the specimens and for getting familiar with species characteristics.